2007
DOI: 10.1007/bf02877769
|View full text |Cite
|
Sign up to set email alerts
|

Probrain Natriuretic Peptide for assessment of efficacy in heart failure treatment

Abstract: N-terminal probrain natriuretic peptide (NT-proBNP) is elevated in patients with heart failure. Numerous clinical trials have evaluated the efficacy of spironolactone in heart failure; however, no studies have directly examined the effects of spironolactone treatment on NT-proBNP level. This study investigated whether NT-proBNP levels decrease with daily spironolactone treatment. The study consisted of 117 adult patients with heart failure. All participants were divided into 3 groups, class I, class II, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In the subset analysis of the EPHESUS, eplerenone had a similar adverse effect profile to placebo, with the exception of increased incidence of hyperkalemia (serum potassium Ն6.0 mmol/L; 1.7-fold) in hospitalized patient groups with a mean age of Ͼ65 years (59). Although not primarily designed as studies of elderly patients, several other studies that included patients who were a mean age of Ն65 years showed that use of spironolactone or eplerenone in this older population was tolerated and safe (55,60,61).…”
Section: Aldosterone Antagonistsmentioning
confidence: 99%
“…In the subset analysis of the EPHESUS, eplerenone had a similar adverse effect profile to placebo, with the exception of increased incidence of hyperkalemia (serum potassium Ն6.0 mmol/L; 1.7-fold) in hospitalized patient groups with a mean age of Ͼ65 years (59). Although not primarily designed as studies of elderly patients, several other studies that included patients who were a mean age of Ն65 years showed that use of spironolactone or eplerenone in this older population was tolerated and safe (55,60,61).…”
Section: Aldosterone Antagonistsmentioning
confidence: 99%
“…In 10 out of 18 trials, patients were seen by a specialist at a clinic (Anguita et al 2010;Berger et al 2010;Eurlings et al 2010;Januzzi et al 2011;Jourdain et al 2007;Lainchbury et al 2009;Murdoch et al 1999;Persson et al 2010;Schou et al 2013;Shah et al 2011;Troughton et al 2000). Most patients were randomized once heart Karlstrom et al 2011;Murdoch et al 1999;Ozkara et al 2007;Persson et al 2010;Schou et al 2013;Shah et al 2011;Stienen et al 2018;Troughton et al 2000). The remainder of the trials combined patients with preserved and reduced ejection fraction (Anguita et al 2010;Berger et al 2010;Carubelli et al 2016;Eurlings et al 2010;Lainchbury et al 2009;Maeder et al 2013;Pfisterer et al 2009).…”
Section: Study Characteristics Of Included Studiesmentioning
confidence: 99%
“…Seventeen out of 18 studies reported mortality at trial completion (Anguita et al 2010;Beck-da-Silva et al 2005;Berger et al 2010;Carubelli et al 2016;Eurlings et al 2010;Felker et al 2017;Januzzi et al 2011;Jourdain et al 2007;Karlstrom et al 2011;Lainchbury et al 2009;Maeder et al 2013;Ozkara et al 2007;Persson et al 2010;Pfisterer et al 2009;Schou et al 2013;Shah et al 2011;Stienen et al 2018;Troughton et al 2000). After extracting the end of trial mortality data, it was deemed inappropriate to conduct a meta-analysis, as the duration of the trial follow up periods differed between the trials.…”
Section: Reduction In Np Levels and Its Association With Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and tolerability of aliskiren in elderly patients has been evaluated in several trials [74][75][76][77][78]. These studies showed that aliskiren lowers BP effectively and is well tolerated, even in patients >75 years old.…”
Section: Antihypertensive Agentsmentioning
confidence: 99%